Sexual Health Dysfunction After Radiotherapy for Gynecological Cancer: Role of Physical Rehabilitation Including Pelvic Floor Muscle Training - Barcellini, Amelia; Dominoni, Mattia; Dal Mas, Francesca; Biancuzzi, Helena; Venturini, Sara Carla; Gardella, Barbara; Orlandi, Ester; Bø, Kari (Frontiers in Medicine, 2022)
Introduction: The present work aims to describe: 1. How side effects of radiotherapy (RT) may impact sexual health in women; 2. the effectiveness of physical rehabilitation including pelvic floor muscle training (PFMT) in the management of sexual dysfunction after RT. Material and methods: Search on PubMed, Web of Science, Scopus, PEDro, and Cochrane were used to identify studies on women treated with radical or adjuvant RT and/or brachytherapy for gynecological cancers with an emphasis on vulvovaginal toxicities and PFMT studies on sexual dysfunction for this group of women. Results: about the first key question, we analyzed 20 studies including a total of 2739 women who reported as the most common side effects: vaginal dryness, stenosis, and pain. Reports of dosimetric risk factors and dose-effect data for vaginal and vulvar post-RT toxicities are scant. Only five studies(three randomized controlled trials-RCTs), were found reporting effect of PFMT alone or in combination with other treatments. The results showed some evidence for effect of training modalities including PFMT, but to date there is insufficient evidence from high quality studies to draw any conclusion of a possible effect. Conclusions: gynaecological toxicities after RT are common and their management is challenging. The few data available for a rehabilitative approach on post-actinic vulvo-vaginal side effects are encouraging. Large and well-designed RCTs with long term follow-up that investigate the effect of PFMT on vulvo-vaginal tissues and pelvic floor muscle function are needed to provide further guidance for clinical management